Luke Treadwell, Buyid Coinage. A die Corpus (322-445 A. H.), Ashmolean Museum, Oxford 2001, XXXIX+247 (Catalogue, Katalog)+172 s. (plates, fotoğraflar). - (:unkn) unknown (My University, 2003)
0
Keywords: Tarih